2007
DOI: 10.1007/s11274-007-9615-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of particle diameter of Lactobacillus acidophilus microcapsule by spray drying and analysis on its microstructure

Abstract: Lactobacillus acidophilus, as a probiotic, is widely used in many functional food products. Microencapsulation not only increases the survival rate of L. acidophilus during storage and extends the shelf-life of its products, but also optimal size microcapsule makes L. acidophilus have an excellent dispersability in final products. In this paper, L. acidophilus was microencapsulated using spray drying (inlet air temperature of 170°C; outlet air temperature of 85-90°C). The wall materials used in this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 19 publications
2
36
0
5
Order By: Relevance
“…As can be seen, the activation energies for the predicted death rates are highly consistent with the measured results. The values found indicate good thermal stability and good storage stability (Zhao et al, 2008), and are in agreement with the literature. Gomes et al (1998) found activation energies ranging from 37.7 to 58.6 kJ/mol for A. acidophilus in reconstituted milk, and Zhao et al (2008) reported an activation energy of 124.43 kJ/mol for encapsulated Lactobacillus acidophilus XH1.…”
Section: Immobilized Cellssupporting
confidence: 90%
“…As can be seen, the activation energies for the predicted death rates are highly consistent with the measured results. The values found indicate good thermal stability and good storage stability (Zhao et al, 2008), and are in agreement with the literature. Gomes et al (1998) found activation energies ranging from 37.7 to 58.6 kJ/mol for A. acidophilus in reconstituted milk, and Zhao et al (2008) reported an activation energy of 124.43 kJ/mol for encapsulated Lactobacillus acidophilus XH1.…”
Section: Immobilized Cellssupporting
confidence: 90%
“…The important challenge of the application of encapsulation in the food industry is the production of large microparticles that can affect the textural and sensorial properties of food products to which they are added [2]. Small microparticles are preferred as they ensure even distribution of the encapsulated probiotic strain that will be active in the final products [38]. The standard size of the microcapsules should be \350 lm [27].…”
Section: Discussionmentioning
confidence: 99%
“…Microparticles larger than 1 mm affect the mouth feel of the foods supplemented with them by resulting in a coarse texture [2]. Beads smaller than 100 lm have been associated with lower encapsulation efficiencies [38], and they do not offer sufficient protection to the encapsulated bacteria in simulated gastric fluids (SGF) when compared with non-encapsulated cells [2]. The PVP:PVAc-CA microparticles have a high encapsulation efficiency (this study) and have previously been proven to significantly improve viability of the encapsulated bifidobacteria in SGF [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ascertain any inhibitory effects of bacteriocin against pathogenic strains bacteria (355.6 AU/mL), 2 mL Lactobacillin XH1 was added to 10 mL suspension of indicator strains of E. coli and 3 h incubation at 37 °C. Then the sample was fixed with 1 % (v/v) glutaraldehyde for 2 h, rinsed by PBS buffer for three times, each time for 5 min, successively with 60 %, 70 % ethanol dehydrated for 10 min, centrifuged, the precipitate was concentrated by vacuum freeze drying, gold-plated metal spraying 90 s, and then examined by electron scanning microscope (Quanta 200 scanning electron microscope of FEI Company, USA) [14].…”
Section: Detecting the Antibacterial Mechanism Of Bacteriocinmentioning
confidence: 99%